2009
DOI: 10.1017/s0007114509991292
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Danish 7-day pre-coded food diary among adults: energy intake v. energy expenditure and recording length

Abstract: Under-reporting of energy intake (EI) is a well-known problem when measuring dietary intake in free-living populations. The present study aimed at quantifying misreporting by comparing EI estimated from the Danish pre-coded food diary against energy expenditure (EE) measured with a validated position-and-motion instrument (ActiReg w ). Further, the influence of recording length on EI:BMR, percentage consumers, the number of meal occasions and recorded food items per meal was examined. A total of 138 Danish vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 16 publications
(21 reference statements)
2
64
0
2
Order By: Relevance
“…A precoded food record (PFR) method was developed to assess the diet of infants and young children between 6 months and 4 years of age (Trolle et al, 2002). We chose a 7-day record rather than a 4-day, because 7 day is more representative of habitual diet, percentage consumers of different foods decrease with fewer days of recording (Biltoft-Jensen et al, 2009), and we wanted to be able to compare the results with The Danish National Survey of Dietary Habits using a similar method (Pedersen et al, 2010). In contrast to the traditional estimated food record method, the PFR uses household measures and photographs for portion size estimation, and is useful for both infants and toddlers.…”
Section: Introductionmentioning
confidence: 99%
“…A precoded food record (PFR) method was developed to assess the diet of infants and young children between 6 months and 4 years of age (Trolle et al, 2002). We chose a 7-day record rather than a 4-day, because 7 day is more representative of habitual diet, percentage consumers of different foods decrease with fewer days of recording (Biltoft-Jensen et al, 2009), and we wanted to be able to compare the results with The Danish National Survey of Dietary Habits using a similar method (Pedersen et al, 2010). In contrast to the traditional estimated food record method, the PFR uses household measures and photographs for portion size estimation, and is useful for both infants and toddlers.…”
Section: Introductionmentioning
confidence: 99%
“…Mean intakes of foods, macro-and micronutrients recorded in the pre-coded FD were calculated by use of the software system GIES developed at the National Food Institute (Søborg, Denmark), including standard recipes, information on portions sizes and data from the Danish Food Composition Database (www.foodcomp.dk) as described previously (6) . Mean intakes of foods and nutrients recorded in the WFR were calculated by use of the same software system and food composition database as for the FD, but including intakes in grams and recipes as reported by the participants.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were asked to fill in the diary prospectively for 7 d, thus not relying on remembering food intake in the past. Ongoing recruitment took place, covering dietary intake for all seasons for the whole population.The pre-coded food diary has previously been validated against an objective measure (energy expenditure assessed by means of a validated position-and-motion instrument), which showed that the ability to rank individuals according to energy intake recorded by the food diary was acceptable (6) . However, the ability to assess intake of specific food groups was not examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A avaliação da ingestão alimentar é de extrema importância na ciência da nutrição, estando, entre as suas diversas aplicações, a identificação de problemas nutricionais a partir do monitoramento da ingestão de alimentos e nutrientes, e a determinação de associações entre a ingestão alimentar e o processo saúde/doença 1 .…”
Section: Introductionunclassified